Explorative study on the role of zakat in achieving equitable wealth distribution tool in Islamic economics. - Sharofiddin, Ashurov; Said, Osman Abdirisak; Othman, Anwar Hasan Abdullah (KPBKL Publication House. Hak Cipta Terpelihara, 2021)
Islam is devoted to global economic brotherhood and social justice. Nevertheless, the Islamic religious principles, as well as for instructions of union and community fairness, would not certainly be significant unless guided. Along with economic justice and Zakat as a social instrument, is considered as the basis of the distribution of wealth in Islam and the most successful tool for eradicating and reducing poverty and other economic and social imbalances. The study is explorative in nature and using a qualitative method with relevant document collection which analyzed the role of Zakat in achieving equitable wealth distribution. The result of the study confirms that if the Zakat fund collected efficiently and disbursed adequately to the deserving members of the society, it will guarantee equitable wealth distribution among Muslim society. As a result, it recommends for zakat institutions to develop a sophisticated platform for an efficient zakat collection and effective distribution mechanism to ensure achieving a fair, unbiased wealth and equitable income distribution.